Contemporary practices of social entrepreneurship: experience of Belarus - Kuchko, Alena E.; Levitckaya, Irina V.; Veremeeva, Nataliya P. (Journal of the Belarusian State University. Sociology, 2019)
The article is based on the results of a sociological research into the peculiarities of social entrepreneurship in Belarus; specificity of its development is revealed; the role and importance of the establishment of the institution of social entrepreneurship is shown; indicators of social entrepreneurship and social enterprise are revealed; the problem of motivation to carry out activities in the field of social entrepreneurship is discussed; methods of creating social enterprises are represented, the main characteristics of existing social enterprises are revealed, as well as the personal characteristics of social entrepreneurs.
Keywords: social entrepreneurship; social partnership; social initiative; social policy